2020
DOI: 10.1111/ejh.13516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of platelets on major thrombosis in patients with a normal white blood cell count in essential thrombocythemia

Abstract: Objectives Cell counts have a significant impact on the complex mechanism of thrombosis in patients with essential thrombocythemia (ET). We recently demonstrated a considerable impact of white blood cell (WBC) counts on thrombotic risk in patients with optimized platelet counts by analysing a large anagrelide registry. In contrast, the current analysis of the registry aimed to estimate the influence of platelet counts on thrombotic risk in patients with optimized WBC counts. Methods Cox regression analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…A previous study reported that platelet >1,000*10 9 /L at initial diagnosis was related to a lower risk of arterial thrombosis ( 42 ). Interestingly, the high platelet in ET patients was more likely to result in thrombotic events when the patients had a normal WBC count ( 43 ). Besides, severe thrombocytosis (>1,500*10 9 /L) in acquired von Willebrand disease might increase the risk of bleeding ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that platelet >1,000*10 9 /L at initial diagnosis was related to a lower risk of arterial thrombosis ( 42 ). Interestingly, the high platelet in ET patients was more likely to result in thrombotic events when the patients had a normal WBC count ( 43 ). Besides, severe thrombocytosis (>1,500*10 9 /L) in acquired von Willebrand disease might increase the risk of bleeding ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible relationship between the normalization of the platelet count and the risk of thrombosis is a matter of debate given the contradictory reported data. 14,15 Second, following the ACC/AHA guidelines, high-risk IPSET-thrombosis patients might be candidates for moderate-intensity lipid-lowering therapy especially if other well-established enhancers such as a family history of arteriosclerotic cardiovascular disease, (2023) 7:8 www.hemaspherejournal.com persistent low-density lipoprotein cholesterol >160 mg/dL, or renal chronic disease are present. 13 The annual incidence of VTEs among individuals in their 40s and 50s ranged from 0.08 to 0.2 per 100 population.…”
Section: Discussionmentioning
confidence: 99%
“…First, the high platelet count found in some patients at the time of thrombosis (data not shown) suggests that poor adherence to treatment or inadequate intensity may have lied behind the vascular event in these patients. However, the possible relationship between the normalization of the platelet count and the risk of thrombosis is a matter of debate given the contradictory reported data 14 , 15 . Second, following the ACC/AHA guidelines, high‐risk IPSET‐thrombosis patients might be candidates for moderate‐intensity lipid‐lowering therapy especially if other well‐established enhancers such as a family history of arteriosclerotic cardiovascular disease, persistent low‐density lipoprotein cholesterol >160 mg/dL, or renal chronic disease are present 13 …”
Section: Discussionmentioning
confidence: 99%
“…White blood cells serve to protect the body from various infectious diseases caused by fungi, viruses, and bacteria. The number and shape of white blood cells is one of the indicators in detecting various types of diseases (Bain, 2017;Buxhofer-Ausch et al, 2021;Negm et al, 2018;Saleem et al, 2022). To find out the type of disease, it is necessary to perform a blood test, which aims to detect, count, and identify white blood cells, and the process is done manually and requires a lot of time.…”
Section: Introductionmentioning
confidence: 99%